First NGS full genome characterization of a hepatitis C virus genotype 7 divergent subtype. - Salmona, M; Caporossi, A; Simmonds, P; Thélu, M; Fusillier, K; Mercier-Delarue, S; De Castro, N; LeGoff, J; Chaix, M; François, O; Simon, F; Morand, P; et al. (Elsevier, 2016)
We report the near full length genome sequence, of an hepatitis C virus isolate from a man originating from Democratic Republic of Congo, whose genotype could not be determined by the routinely used sequence technique.The near-complete genome sequence of this variant BAK1 was obtained by the association of two next generation sequencing technologies.Evolutionary analysis indicates that this isolate BAK1 could be the first reported strain belonging to a new HCV-7b subtype. This new subtype has been incorrectly identified as genotype 2 by Versant HCV Genotype 2.0 assay (LiPA).The requirement of three independent isolates has been filled and a new subtype can be assigned. More examples of HCV-7 are required to better understand its origin, its pathogenicity and its relationship with genotype 2.